Gender shift in the pragmatics of addresses - Μ. A. Krongauz; I. V. Fufaeva (Шаги)
The purpose of this article is to summarize a number of specific pragmatic changes characteristic of the use of Russian terms of address, which we propose to call a gender shift. Gender shift in the pragmatics of addresses consists in their non-standard use in the gender aspect, when addresses to women, such as mamochka ‘mommy’, matushka ‘mother’, are used towards men, and typical addresses to men, such as tovarishch ‘comrade’, druzhochek ‘buddy’, chuvak ‘dude’, are employed with women. It is noted in the article that gender shift in pragmatics of terms of address occurs under certain conditions and signals specific types of attitudes towards the interlocutor: patronizing, as to an equal, friendly, etc. Thus, the use of feminine terms of address to men is associated with a patronizing position of the speaker, as a rule, older in age and higher in status. These terms of address express an affectionate, patronizing, good-natured attitude of the elder towards the younger. The use by men of familiar and even masculine terms of address to women can express an attitude towards a woman not just as an equal, but also as «their brother», acceptance into a community such as a «men’s club». At the same time, the use of familiar, friendly male terms of address in communication between girls may reflect a desire to transferred to the female community relationships similar to relationships in informal male communities. In all these cases, we are not talking about gender-neutral terms of address, but about a gender shift associated with desemantization (semantic depletion), which is felt by native speakers as a living process. Research methods were used to analyze corpora and conduct surveys.